Perjanjian Indonesia-Malaysia Terhadap Tki (Tenaga Kerja Indonesia) Yang Ditinjau Dari Segi Hukum Dan Ekonomi - Claudya Florenza Br Rajagukguk; Annisa Ayu Syahrani; Tamaulina Br Sembiring (PT. ALHAFI BERKAH INDONESIA, 2024)
In social life, humans are called social creatures, which means that humans cannot live alone. Humans need help or assistance from other humans in order to survive. Just like humans, countries cannot stand alone without help from other countries. The independence of a country requires recognition from other countries so that the country can be said to be legally an independent country. In fact, not only in terms of independence, the country needs the role of other countries to be able to grow and strengthen the country. Due to the awareness that a country cannot stand alone, an agreement is made between one country and another country. This agreement is called an